Foreword: The Dynamic Evolution of International Law – Rise or Decline? - McLachlan, Campbell (Victoria University of Wellington Law Review, 2018)
This is the foreword to the special issue of the Victoria University of Wellington Law Review presenting an edited collection of articles from leading voices in the field of public international law – scholars, judges and practitioners – that reflect on the different dimensions of the problem of change in international law.